1997
DOI: 10.1111/j.1699-0463.1997.tb05066.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of onset in an insulin‐dependent diabetes mellitus model, NOD mice, by oral feeding of Lactobacillus casei

Abstract: Prevention of onset in an insulin-dependent diabetes mellitus model, NOD mice, by oral feeding of Lactobacillus casei. APMIS 105: [643][644][645][646][647][648][649] 1997.The effects of Lactobacillus casei (LC) on the onset of diabetes in an insulin-dependent diabetes mellitus model, nonobese diabetic (NOD) mice, were examined. From the age of 4 weeks, female NOD mice were fed a diet of either standard laboratory chow (n= 12) or the same chow containing 0.05% weight heat-killed cells of LC (n= 12), and the ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
128
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(135 citation statements)
references
References 31 publications
4
128
0
3
Order By: Relevance
“…While the bacterium is known to be a strong Th1-type cytokine inducer (32), of which the active component was proposed to be LTA (12), it exerts anti-inflammatory activity against diabetes mellitus (26) and inflammatory bowel disease (24,25) in animal models. It was shown that the cell wall preparation containing PS and PG could be the active component of the anti-inflammatory activity (25).…”
mentioning
confidence: 99%
“…While the bacterium is known to be a strong Th1-type cytokine inducer (32), of which the active component was proposed to be LTA (12), it exerts anti-inflammatory activity against diabetes mellitus (26) and inflammatory bowel disease (24,25) in animal models. It was shown that the cell wall preparation containing PS and PG could be the active component of the anti-inflammatory activity (25).…”
mentioning
confidence: 99%
“…Improvement of the Th1/Th2 balance and downregulation of IL-6 production were proposed to be the underlying mechanisms. 22,23 LcS has also been shown to be effective in experimental models of autoimmune diseases such as arthritis, 24 type I diabetes 25 and systemic lupus erythematosus. 26 These multifactorial clinical efficacies suggest the possibility that LcS can not only augment host immune defense against cancer and infection, been used for making fermented dairy products for more than 70 years.…”
Section: Potent Induction Of Il-12 and Augmentation Of Host Immune Dementioning
confidence: 99%
“…A role for bacteria in the onset of diabetes has been shown in two murine models. For example, feeding probiotic bacterial strains, usually lactic acid bacteria, to non-obese diabetic mice or biobreeding diabetesprone (BB-DP) rats can delay or prevent diabetes (Matsuzaki et al, 1997;Calcinaro et al, 2005;Yadav et al, 2007). Feeding antibiotics to nonobese diabetic mice or BB-DP rats can also increase survival in these models Schwartz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%